Spatial Distribution of Availability to Drinking Water and Sanitation Facilities: A District Level Analysis, Haryana (2011): Exploring Disparities in Water and Sanitation Facilities (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Drinking water and sanitation is the basic necessity of a community. It plays a vital role in improving health and quality of life. Adequate water is basic need of our life. Sanitation is the hygienic mean of promoting health through prevention of human contact with the hazard of wastes. Hazards can be physical, microbiological and chemical agents of diseases. Hygienic means of prevention can be by using engineering solution, simple technologies or even by personal hygiene practices. Without proper hygiene and contaminated water cause diarrhoea, cholera and other human killer diseases. According to the Census of India 2011, 833 million people (69.84) are still living in the villages and data also shows that still around 70 of India’s rural or slum population are exposed to water-borne and vector -borne diseases due to lack of basic sanitation facility, unsafe water and unhygienic condition. The condition of drinking water and sanitation facilities in Haryana is good comparatively other states. The study reveals that in urban Haryana districts Gurugram (2.13) and Rohtak ( 2.12) have better drinking water and sanitation facilities it may be possible because the development of these districts are due to near of Country Capital along with eastern part and two districts locate along with State capital from northern part of the state. But the situation is still disappointing in case of Mewat and Mahendergarh districts because despite of development, these are more deprived are more deprived. It is also noted that these districts locate in southern part of the state. In urban Haryana, Ambala (4.33) and Punchkula (3.40) have good condition whereas Mewat (-5.33) is in bottom. It may be caused by dominance of sandy soil and less development industrial development in south western and western part as compare to other districts.